POSITION AND RESPONSIBILITIES OF ADDICTION COUNSELOR IN THE FRAMEWORK OF REHABILITATION GUIDANCE FOR NARCOTICS USING PRISONERS AT CLASS IIB BANYUASIN NARCOTICS PRISON - Zeland Muhammad Barr; Mulyadi Tanzili; Syamsul Syamsul (Universitas Nusa Cendana, 2026)
This study examines the role and responsibilities of addiction counselors in the rehabilitation of narcotics inmates at the Class IIB Banyuasin Narcotics Prison. It highlights the shifting function of correctional institutions from purely punitive environments to centers focused on recovery and reintegration. Using a qualitative descriptive approach, data were collected through non-participant observation, in-depth interviews with counselors and inmates, and analysis of relevant documents. The data were then analyzed thematically to generate comprehensive insights. The findings show that addiction counselors hold a legally mandated and strategically important role within the rehabilitation system. They act as a bridge between institutional security and therapeutic processes. Their work involves structured stages of assessment and intervention, implemented through the Therapeutic Community approach, which includes individual, group, and family counseling. The program demonstrates strong effectiveness, reflected in high levels of participant compliance and successful recovery outcomes, including sustained abstinence from drug use among inmates involved in the program. In conclusion, addiction counselors play a crucial role in supporting inmate recovery, maintaining institutional stability, and advancing the rehabilitative function of correctional facilities. Strengthening their capacity and institutional support is essential to ensure the sustainability and effectiveness of narcotics rehabilitation programs. Keywords: Addiction Counselor; Rehabilitation; Narcotics Prison